“Flex”, a digital telco that will disrupt the Malaysian telecom market - Amir, Alfie Shahrein (2023)
Business Concept: Like how Airbnb and Uber disrupted the hospitality and the public transportation market respectively, Flex will be a digital-native telco that provides telecom services to digital-native customers or Gen-Z, without owning any assets. With a cost-focus and differentiation-focus strategy, Flex will challenge the incumbents through its flexible services and offer values that matter to Gen-Z. This includes potential savings through its usage-based billing as opposed to the volume-based plans available in the market today, end-to end digital customer lifecycle, personalised experience as well as environmental and ethical values.